2022
DOI: 10.1002/ece3.9639
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SNP density on quantitative genetic analyses of body size traits in a wild population of Soay sheep

Abstract: Understanding the genetic architecture underpinning quantitative traits in wild populations is pivotal to understanding the processes behind trait evolution. The ‘animal model’ is a popular method for estimating quantitative genetic parameters such as heritability and genetic correlation and involves fitting an estimate of relatedness between individuals in the study population. Genotypes at genome‐wide markers can be used to estimate relatedness; however, relatedness estimates vary with marker density, potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…0.019) between adult foreleg length and adult hindleg length (Bérénos et al 2014 ), inclusion of a thresholded GRM at t = 0.1 is significant for adult foreleg length and not adult hindleg length. However, in a recent genome-wide association study of this population, we found two peaks on chromosomes 7 and 9 that were significantly associated with adult foreleg length but not with adult hindleg length (James et al 2022 ). It is possible that family-associated variation such as epistasis and dominance are acting upon these two regions, resulting in the inclusion of the thresholded GRM being significant for adult foreleg length but not adult hindleg length.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…0.019) between adult foreleg length and adult hindleg length (Bérénos et al 2014 ), inclusion of a thresholded GRM at t = 0.1 is significant for adult foreleg length and not adult hindleg length. However, in a recent genome-wide association study of this population, we found two peaks on chromosomes 7 and 9 that were significantly associated with adult foreleg length but not with adult hindleg length (James et al 2022 ). It is possible that family-associated variation such as epistasis and dominance are acting upon these two regions, resulting in the inclusion of the thresholded GRM being significant for adult foreleg length but not adult hindleg length.…”
Section: Discussionmentioning
confidence: 62%
“…Genotypes with a probability of <0.99 were excluded, resulting in, 419,281 autosomal SNPs remaining for 8557 individuals (4035 females, 4452 males). We have previously shown that imputation does not affect heritability estimates for these traits in this population (James et al 2022 ).…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations